A STUDY OF MALE AND FEMALE GENITALIA: A TAXONOMIC TOOL FOR THE IDENTIFICATION OF SAND FLY (Diptera: Phlebotomidae) - BHATNAGAR, NEHA; MAHESHWARI, GEETA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Sand flies are minute blood sucking flies and are of considerable medico-veterinary significance as these are the vector of several diseases viz., Leishmaniasis, Bartonallosis and viral diseases such as Sand fly fever, Chandipura Encephalitis etc. They are found throughout the world’s tropical and subtropical region. The correct identification of the species of this fly is very important for its control and epidemiological study. The structure of male and female genitalia is species specific and show extraordinary diversity. Thus the male and female genitalia are an important source of diagnostic features to separate the specimen at generic as well as specific level. Male genital armature of Phlebotomidae has occupied a right place in the studies of Phlebotomidae taxonomy but female genitalia is neglected by taxonomist as they used only the internal female genital structure in the Phlebotomid taxonomy. From the present investigation it has been revealed that both male and female genitalia show a large number of variation both externally and internally due to this these genital characters in the family Phlebotomidae are very reliable tool for taxonomic studies and these characters can easily be used in the formulation of dichotomus keys for identification of different species of sand flies. The present investigation will be significant for the search and description of new species of India.